Kneza, mesti - Gudović, Milosav (Primerjalna književnost, 2018)
This article is dedicated to the group of religious-philosophical motifs of Hölderlin%s late hymn, Celebration of Peace, the center of which belongs to the character of Christ as "the prince of the festival". We arrive at a possible explanation of this poetic image by comparative reading of Dostoyevsky. To Lev Nikolaevich Myshkin, the main character of the novel The Idiot, the author assigned the role of a prince as well. To the external and accidental kinship of these two artistic figures, which originated in different literary and intellectual frameworks, our interpretation attaches an essential characteristic in common: a literary conceptualization of the kenotic act of God and (hu)man. We took the term "two cities" from Sergei Bulgakov's book of the same name (Dva grada).
Keywords: Hölderlin, Friedrich, 1770-1843; Dostoevskij, Fedor Mihajlovič, 1821-1881; literature and religion; literatura in religija; poetic image; Holbein, Hans; Jesus Christ; pesniška podoba; kenosis; Jezus Kristus; kenoza